Analysis of Local Tax Efforts in Supporting Increasing Ponorogo Regency’s Original Local Government Revenue - Arif Hartono; Yeni Alvionita (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2021)
This research was conducted at the Agency for Revenue, Financial Management, and Regional Assets of Ponorogo Regency, which aims to make an analysis of local tax efforts (tax effort) in supporting the increase in Ponorogo Regency's Original Local Government Revenue. This study uses analysis methods of local tax elasticity, analysis of local tax contributions, analysis of local tax effectiveness, and analysis of local tax efforts. The final results of this study showed that the average elasticity of local taxes during 2014-2020 is 2.30, meaning that the elasticity of local taxes in Ponorogo Regency falls within the elastic criteria. This shows the elasticity relationship between the growth rate of local taxes and the growth of GDP towards Local Revenue. The average rate of local tax contributions during 2013-2020 was 26.91% with moderate criteria. This means that local tax receipts during 2013-2020 are not the largest source of Local Revenue, as it only provides income to Local Revenue of 26.91% on average during the research year. The average rate of effectiveness of local taxes during 2013-2020 was 116.84% with very effective criteria. This means that local tax receipts during 2013-2020 illustrate the ability of local governments in realizing local revenues with targets set based on the potential of the regional rill. The average tax effort for 7 years (2014-2020) is 1.89%. This shows that the level of local tax efforts in Ponorogo regency has decreased over the last 7 years. The decrease in the level of tax effort occurs due to the decrease in GDP. Based on the results of the analysis, the Regional Government of Ponorogo Regency through the Original Local Government Revenue, Financial and Asset Management Agency can continue to improve the local tax collection mechanism because it is proven to be able to provide a large contribution to Original Local Government Revenue.